Naval crossfire: a comparative analysis of iron projectiles from mid-18th to early 19th centuries European warships - Ciarlo, Nicolás Carlos (2015)
The ordnance of early Modern main maritime powers (i.e. Great Britain, France, and Spain) played an important role in conflictsfor supremacy of the seas. Therefore, it was subjected to various innovation processes, in order to improve their efficiency. Thisstudy presents the characterization results of an array of iron projectiles recovered from the following sites: 1) the sloop-of-warHMS Swift (1763-1770), 2) the Spanish ship Triunfante (1756-1795), 3) the French ship Bucentaure (1804-1805), and 4) the siteDeltebre I (1813). Based on data obtained using Optical Microscopy (OM), Scanning Electron Microscopy (SEM), and EnergyDispersive X-ray Spectrometry (EDXRS), a comparative analysis was performed, in order to clarify the technological differencesand similarities that were present in the projectiles used by the mentioned ships.